1987
DOI: 10.2307/3324850
|View full text |Cite
|
Sign up to set email alerts
|

Whom Do You Trust? An Analysis of Executive and Congressional Economic Forecasts

Abstract: Economic forecasts play an increasing role in U.S. budgetary and fiscal policies. This paper analyzes the accuracy and bias of economic forecasts prepared by the Executive Branch and Congress. Short-run forecasts by the Executive Branch for the forthcoming year do not appear biased. They are as accurate as private forecasts and the forecasts of the Congressional Budget Office (CBO); they are not sensitive to political factors such as the size of the deficit. At the same time, the accuracy o f Executive branch'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 2 publications
0
20
0
Order By: Relevance
“…Thus we expect 3 See Poterba (1994) and Rubin (2006). 4 Kamlet et al (1987) examine the accuracy of Executive Branch and Congress forecasts of real GNP growth, inflation, and unemployment for the years 1962 to 1984. The authors expect forecasts to be more optimistic in years when an unbiased forecast would predict a lower level of growth.…”
mentioning
confidence: 99%
“…Thus we expect 3 See Poterba (1994) and Rubin (2006). 4 Kamlet et al (1987) examine the accuracy of Executive Branch and Congress forecasts of real GNP growth, inflation, and unemployment for the years 1962 to 1984. The authors expect forecasts to be more optimistic in years when an unbiased forecast would predict a lower level of growth.…”
mentioning
confidence: 99%
“…Their ®ndings supported the earlier work and found that forecast accuracy is enhanced in an environment with strong institutional pressures and highly partisan politics. Kamlet, Mowery, and Su (1987) found no evidence that partisan politics biased short-term economic forecasts by the executive branch or Congress. On the other hand, Smith (1984, 1989) and Feenberg et al (1989) discovered a conservative bias or underestimation in state revenue forecasts explained by the need to generate a hedge or buer against future revenue uncertainty.…”
Section: Forecasting Researchmentioning
confidence: 84%
“…Kamlet, Mowery, and Su (1987) compare one-yearahead and multi-year-ahead forecasts from CBO, OMB, their own ARIMA model, and the ASA/NBER survey for the real growth rate, inflation rate, and unemployment from 1976 to 1984. 3 They find that neither agency outperforms the other for short-term forecasts.…”
Section: Literature Reviewmentioning
confidence: 99%